2021
DOI: 10.1002/ptr.7032
|View full text |Cite
|
Sign up to set email alerts
|

Berberine—A potent chemosensitizer and chemoprotector to conventional cancer therapies

Abstract: Chemotherapy and radiotherapy are mainstay treatments for cancer patients. However, their clinical outcomes are highly limited by the resistance of malignant tumors to these therapies and the incurrence of serious damages in vital organs. This in turn necessitates the development of adjunct drugs that overcomes chemo/radioresistance in refractory cancers and protects vital organs from the cytotoxic effects of cancer therapies. In recent years, Berberine (BBR), a natural isoquinoline alkaloid has garnered more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 100 publications
0
24
0
Order By: Relevance
“…In MCF-7 breast cancer cells and the doxorubicin-resistant (ADR) cells MCF-7 (MCF-7/ADR), BBR was recently identified as an autophagy suppressor, inhibiting the formation of autophagosomes in MCF-7/ADR cells [ 51 ]. Berberine treatment blocked the accumulation of the LC3II protein, which is associated with autophagy, leading to accumulation of the signaling adaptor p62 protein, decreasing cell proliferation, and reversing doxorubicin resistance [ 52 ].…”
Section: Anticancer Perspectivesmentioning
confidence: 99%
“…In MCF-7 breast cancer cells and the doxorubicin-resistant (ADR) cells MCF-7 (MCF-7/ADR), BBR was recently identified as an autophagy suppressor, inhibiting the formation of autophagosomes in MCF-7/ADR cells [ 51 ]. Berberine treatment blocked the accumulation of the LC3II protein, which is associated with autophagy, leading to accumulation of the signaling adaptor p62 protein, decreasing cell proliferation, and reversing doxorubicin resistance [ 52 ].…”
Section: Anticancer Perspectivesmentioning
confidence: 99%
“…Berberine has also been reported to be a potent chemosensitizer and chemoprotector for conventional cancer therapies; it sensitizes tumor cells to chemotherapy and radiotherapy [ 26 ]. Berberine modulates various signaling pathways, including PI3K/Akt, MAPKs, AMPK, STAT3, NF-κB, EGFR, ROS, and HIF-1α, to sensitize cancer cells to a broad spectrum of cancer therapies [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Berberine has also been reported to be a potent chemosensitizer and chemoprotector for conventional cancer therapies; it sensitizes tumor cells to chemotherapy and radiotherapy [ 26 ]. Berberine modulates various signaling pathways, including PI3K/Akt, MAPKs, AMPK, STAT3, NF-κB, EGFR, ROS, and HIF-1α, to sensitize cancer cells to a broad spectrum of cancer therapies [ 26 ]. In addition, blocking of programmed cell death-1 (PD-1)/programmed cell death ligand-1 (PD-L1) has become a major cancer immunotherapy in various human cancers including NSCLCs [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the standard cancer research would be to identify either pharmacologic or lifestyle interventions that could prevent the onset of prostate cancer (Chandrasekaran Kirubhanand et al .,2020). Studies have shown that some natural foods' intake decreases the risk of various dreadful diseases including diabetes, cancer, etc (Cryns V, Yuan J 1988,Desai AG et al,2008,Devarajan N et al,2021,D'Hooge,et al .,1996,Fischer U,Schulze-Osthoff K 2005 Intrinsic apoptotic pathway is mainly governed by Bcl-2 family proteins. This family contains both pro-and anti-apoptotic proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, approximately 28% of modern medicines are derived from medicinal plants (Janardhanan S et al, 2020,Jayaraman S et al,2021Khan KH,et al,2015,Kim, H. Get al, 2012,KumarS, et al 2017. There are several drugs derived from the plant origin are used in market to treat cancer which includes vinca alkaloidsvinblastine and vincristine, epipodophyllotoxins (etoposide, teniposide), taxanes (paclitaxel, docetaxel), and camptothecin derivatives (topotecan, irinotecan) (Li.S, Wang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%